Bacillus subtilis as growth-promoting rhizobacteria co-inoculated on Bradyrhizobium-treated soybean seeds in the planting furrow - Galbieri, Rafael; Alves de Oliveira, Jéssica; França Negri, Bárbara; Souza Boldt, Alberto; dos Santos Rizzi, Ueverton; Belot, Jean Louis (Revista Ceres, 2023)
Plant growth-promoting rhizobacteria (PGPR) can ensure the sustainability of agricultural growth. The objectives of this study were to characterize and determine the effects of Bacillus subtilis, isolate IMA Bs/170005, applied as co-inoculant in the soybean planting furrow. In all treatments, the seeds had been pre-inoculated with Bradyrhizobium japonicum. The experiments were carried out in a greenhouse, and in the field. Different doses of formulated (8.108 spores mL-1) product with B. subtilis (0; 0.2; 0.4; 0.8; 1.2; 1.6 and 2.0 L ha-1) were tested. The isolate proved efficient for in vitro auxin production. Under greenhouse conditions, the response to B. subtilis co-inoculation consisted of an increase of up to 26% in length of the root system. In the field, co-inoculation in the furrow proved beneficial for crop growth and yield and can be recommended. The best response rate was 0.4 L ha-1. At this dose, averaged over 20 and 40 days after sowing and compared to the control with Bradyrhizobium inoculation alone, increases of 5.3% were observed for plant height, 14.8% for shoot fresh weight, 14.1% for shoot dry weight, 8.5% for root dry weight and 6.5% for soybean yield, demonstrating the efficiency of this B. subtilis isolate as a PGPR.